2000
DOI: 10.1016/s0014-5793(00)01765-8
|View full text |Cite
|
Sign up to set email alerts
|

Density‐dependent induction of TNF‐α release from human monocytes by immobilized P‐selectin

Abstract: P-selectin purified from human platelets, when immobilized on a solid surface, induced monocytes to release tumor necrosis factor-K K (TNF-K K). The induction of TNF-K K release was dependent on the concentration of P-selectin used for the immobilization, and the maximal stimulation was observed when the plate was coated with 0.3 W Wg/ml of P-selectin. Use of either a higher or a lower concentration of P-selectin for the plate-coating was found to elicit less TNF-K K release, although the higher concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Another anti-P-selectin Ab (2D7, IgG1) [13] was purified from conditioned medium of hybridoma in our laboratory. For purification of P-selectin, mAb 2D7 was conjugated to CNBr-activated Sepharose 4B (GE Healthcare) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another anti-P-selectin Ab (2D7, IgG1) [13] was purified from conditioned medium of hybridoma in our laboratory. For purification of P-selectin, mAb 2D7 was conjugated to CNBr-activated Sepharose 4B (GE Healthcare) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The antibody (Ab) engagement of PSGL-1 upregulates the expression of colony-stimulating factor (CSF)-1 mRNA in Jurkat leukemic cells [12]. Our previous study also demonstrated that P-selectin immobilized on a culture plate effectively induced monocytes to secrete tumor necrosis factor (TNF)-α [13]. Cytokines secreted from monocytes have been shown to regulate various types of immune responses and inflammatory/allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that because our experiments are performed in a plateletfree environment might be one reason for this observation, because P-selectin, which can be found on the surface of activated platelets, has been identified as a relevant inducer of TNF-␣ release from monocytes. 42 A recent publication assigns platelets a relevant role in TRALI induced by monoclonal antibodies against MHC I in a murine model. 43 It is conceivable that further monocyte activation by platelets might trigger TRALI under certain conditions in vivo.…”
Section: Hla Class II Antibody-inducedmentioning
confidence: 99%
“…37 Similarly, one possibility is that the P-selectininduced phosphatidylserine exposure is not a direct effect of signaling through ligated PSGL-1, but rather the effect of mediators (eg, tumor necrosis factor-␣) released by the monocyte when stimulated with P-selectin. 10 The small amount of phosphatidylserine expression on THP-1 cells incubated with unstimulated platelets very likely resulted from a slight degree of activation of the platelets that occurred during their preparation. This interpretation is supported by the observation that an anti-PSGL-1 antibody reduced phosphatidylserine exposure in the cells incubated with activated platelets to levels below those observed in THP-1 cells incubated with unstimulated platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of P-selectin to its main counter-receptor on monocytes, P-selectin glycoprotein ligand-1 (PSGL-1), leads to monocyte activation marked by the conformational activation of the ␤-2 integrin, MAC-1, 9 the synthesis and release of various cytokines, 10 chemokines, 11 and of reactive oxygen species. 12 Importantly, binding of P-selectin to PSGL-1 on monocytes also induces the expression of tissue factor (TF), 2 the main initiator of coagulation in vivo.…”
Section: See Page 877mentioning
confidence: 99%